Fundamentos da vinculatividade dos precedentes judiciais brasileiros - Negrão, João Vitor Ferreira de Faria (2019)
This paper aims to collaborate with the identification of the binding nature of Brazilian judicial precedents. For this, the current stage of the Law is verified, ass in Brazil, especially the alteration of the procedural systematics introduced by the Law no 13.105 2015, in accordance with the Federal Constitution of 1988, to understand the existence of binding precedents, positived by the novel process code. It begins with a brief historical analysis of the common law legal system and the brazilian juridical tradition, revealing the behavior of judicial precedents in each system, and, in the end, it is identified, through the constitutional principle of equality and the new procedural, by the new civil process code, if the Brazilian precedents binds. It is concluded that the delimitation of a brazilian own dogmatic of judicial precedents is essential, once that binding of national judicial precedents exists. It will be based on the hypothetical-deductive approach method and the indirect research technique with study of sources of primary and secondary research.